2018
DOI: 10.1002/isd2.12049
|View full text |Cite
|
Sign up to set email alerts
|

Plans and “off‐plan activities”: Exploring the roles of data and situated action in health planning in Burkina Faso

Abstract: Implementation of health management information systems (HMIS) has gone hand in hand with a growing global demand for high-quality data. While this has sustained HMIS implementation, it has also promoted a data-centric assumption that better data leads to better action on health. An example is health managers envisaged using HMIS data to make action plans for health service delivery. The paper draws on an in-depth study of practices of health data use in Burkina Faso to explore this relationship further. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Of the 55 articles that presented challenges in RHIS data use, 21 (38%) described technical issues, which occurred across the information needs, data collection, data transmission, data processing/analysis and dissemination of processed information stages. At the information needs stage, the majority of technical issues were related to limitations with the data collection forms, which prevented researchers from accurately assessing the current state of health in a population (Soeung et al, 2007; Qazi, Ali and Kuroiwa, 2008; Scott et al, 2017; Rasmussen, 2018). In Peru, for example, Iguiñiz-Romero and Palomino (2012) identified the poor structure of forms as a major challenge to collecting high-quality data, finding an absence of standardised case definitions, as well as information on patient characteristics such as sex.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 55 articles that presented challenges in RHIS data use, 21 (38%) described technical issues, which occurred across the information needs, data collection, data transmission, data processing/analysis and dissemination of processed information stages. At the information needs stage, the majority of technical issues were related to limitations with the data collection forms, which prevented researchers from accurately assessing the current state of health in a population (Soeung et al, 2007; Qazi, Ali and Kuroiwa, 2008; Scott et al, 2017; Rasmussen, 2018). In Peru, for example, Iguiñiz-Romero and Palomino (2012) identified the poor structure of forms as a major challenge to collecting high-quality data, finding an absence of standardised case definitions, as well as information on patient characteristics such as sex.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that all data analyses were undertaken at district or regional level, as PHC workers did not perform any analysis or interpretation of collected data at local level. As Rasmussen (2018) [ 53 ] pointed out, the inability of actors to analyse and work with data at the local level may negatively affect the quality of the data reported to the district level. In this study, we noted several forms with missing or inadequate data submitted to the District level which, given local analysis, may have been noted.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that all data analyses were undertaken at district or regional level, as PHC workers did not perform any analysis or interpretation of collected data at local level. As pointed out by Rasmussen [53], the inability of actors to analyze and work with data at the local level may negatively affect the quality of the data reported to the district level. In this study, we noted several forms with missing or inadequate data submitted to the District level which, given local analysis, were likely to have been noted.…”
Section: Processes Categoriesmentioning
confidence: 99%